BRI and beyond: Comparative possibilities of extended Chinese urbanisation. (26th October 2021) - Bunnell, Tim
Abstract: In terms of spatial imaginaries and as physical infrastructure, the Belt and Road Initiative (BRI) spurs new geographies of comparative urban study. Irrespective of whether it is the primary driver for developments carried out in its name, 'the BRI' is a label that serves to bring previously unassociated project sites and non‐place‐based infrastructural developments into comparative relation. This paper considers some of the possibilities presented by the BRI for comparative urban studies in – and from – Asia. Building upon insights from postcolonial urban studies, planetary urbanisation and inter‐Asia cultural studies, I sketch two key possibilities of the BRI as (comparative urban) method. The first concerns the BRI as a series of openings to much (spatially) wider and historically deeper forms of comparison. Second, I argue that BRI as method impels forms of urban comparison beyond conventionally territorialised units of analysis at a variety of scales, including both the city and the (area studies) region.